2016
DOI: 10.15171/jarcm.2016.038
|View full text |Cite
|
Sign up to set email alerts
|

Blunt abdominal trauma and organ damage and its prognosis

Abstract: Citation: Abri B, Shams-Vahdati S, Paknezhad S, Sepehri-Majd P, Alizadeh S. Blunt abdominal trauma and organ damage and its prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 15 publications
3
12
2
Order By: Relevance
“…Kidney and splenic injuries were more common in the non-penetrating group. (11) The mortality rate in the present study was 3.3%, which is quite similar to the finding by the Abri et al, (8) Siddique et al, (11) Davis et al, (14) and Khan et al (15) Mehta et al in a study conducted among blunt trauma patients reported a mortality rate of 4%. (3)…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Kidney and splenic injuries were more common in the non-penetrating group. (11) The mortality rate in the present study was 3.3%, which is quite similar to the finding by the Abri et al, (8) Siddique et al, (11) Davis et al, (14) and Khan et al (15) Mehta et al in a study conducted among blunt trauma patients reported a mortality rate of 4%. (3)…”
Section: Discussionsupporting
confidence: 90%
“…In a study by Abri et al among blunt abdominal trauma patients 63.9% were male. (8) The current study also has reported a higher percentage of males that get affected by the abdominal trauma compared to the females. This may be due to the reason that males are more involved with outdoor activity.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…There are also other causes such as violence, fighting, and sports. [1][2][3] Department of General Surgery, School of Medicine Udayana University/Sanglah General Hospital, Denpasar-Bali, Indonesia…”
Section: Introductionmentioning
confidence: 99%
“…kidney and spleen), mesenteric tear/s, unexplained moderate to large amounts of free fluid (200-500mls), and failed non-operative management. 2,5…”
Section: Introductionmentioning
confidence: 99%